Adherence and the Lie in a HIV Prevention Clinical Trial. Issue 6 (1st November 2016) - Stadler, Jonathan; Scorgie, Fiona; van der Straten, Ariane; Saethre, Eirik
ABSTRACT: The lie has been presented as a performance that protects identities against moral judgment in the context of power imbalances. We explore this assertion from the perspective of a pre-exposure prophylaxis trial to prevent HIV for African women in South Africa, in which context biological evidence of widespread lying about product adherence was produced, resulting in a moral discourse that opposed altruistic and selfish motivations. In this article, we seek to understand the meaning of the lie from the perspective of women trial participants. Seeing the trial as representing a hopeful future, and perfect adherence as sustaining their investment in this, participants recited scripted accounts of adherence and performed the role of the perfect adherer, while identifying other participants as dishonest. Given that clinical trials create moral orders and adherence is key to this, we argue that women embraced the apparatus of the clinical trial to assert their moral subjectivities.